2014
DOI: 10.1111/zph.12113
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Antibody Prevalence in Wildlife in Poland

Abstract: Hepatitis E is an important public health problem mostly in developing but occasionally also in industrialized countries. Domestic and wildlife animals are considered reservoirs of the hepatitis E virus (HEV). Since no information on the prevalence of autochthonous HEV infections in human and animal in Poland is available, the aim of the study was to investigate the HEV seroprevalence of different wildlife species as potential virus reservoirs in the country. No HEV antibodies were found in any of the sera col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
35
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 25 publications
13
35
0
3
Order By: Relevance
“…Larska et al (9) demonstrated that the percentage of seropositive wild boars was 44.4% and HEV antibodies were found in the animals from 52 out of 94 hunting sites. Significant variation in the percentages of seropositive wild boars from different provinces was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larska et al (9) demonstrated that the percentage of seropositive wild boars was 44.4% and HEV antibodies were found in the animals from 52 out of 94 hunting sites. Significant variation in the percentages of seropositive wild boars from different provinces was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The highest percentages of seropositive wild boars of 88.2% and 84.2% were found in the West Pomerania and Lower Silesia Provinces, respectively. In the study by Larska et al (9), HEV antibody prevalence in wildlife in Poland was determined in 11 out of 16 provinces of Poland. The samples were collected in 2012-2013 during the classical swine fever monitoring programme.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, an apparent seroprevalence of 10.4% was observed in 968 red deer (Boadella et al 2010), in Italy -5.6% of 54 red deer (Mazzei et al 2015b), and in Belgium -1% of 189 red deer (Thiry et al 2015). The HEV specific antibodies were detected in serum of 5% of 38 red deer and none of 8 roe deer studied in Netherlands (Rutjes et al 2010); whereas in Poland, no antibodies were detected in 118 red deer and 38 roe deer serum samples (Larska et al 2015). We have estimated a 1.2% HEV seroprevalence in Lithuanian roe deer and this result was partially in line with Thiry et al (2015) who determined 3% of 235 roe deer to be seropositive in Belgium.…”
Section: Discussionmentioning
confidence: 97%
“…A Polish study determined 44.4% of HEV antibodies in the serum of wild boar from 11 different Polish provinces (Larska et al 2015), while a Spanish study found an overall seroprevalence of 42.7% in wild boar population from South Central Spain, whereas IgG seroprevalence ranged from 0% to 63.3% depending on geographical region. On the other hand, overall seroprevalence in wild boar population in Switzerland and Croatia was reported to be 12.5% (Burri et al 2014) and 12.3% (Prpic et al 2015) of all tested samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…W Europie seroprewalencja wynosi od 12% w populacji tych zwierząt w Holandii do 42,7% w Hiszpanii (13,57). W Polsce badania przeprowadzane na populacji dzików pochodzących z obszaru środkowej i zachodniej części kraju wskazały na obecność przeciwciał u 44,4% badanych zwierząt (30). Przeciwciała anty-HEV wykazano również u jeleni i saren, jednak seroprewalencja w europejskiej populacji dzikich przeżuwaczy nie przekraczała 6,8% (46,70).…”
Section: Hev U Ptakówunclassified